2020
DOI: 10.1101/2020.05.27.20115113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Lockdown in a Kenyan Informal Settlement: Impacts on Household Energy and Food Security

Abstract: A COVID-19 lockdown may impact household fuel use and food security for ~700 million sub-Saharan Africans who rely on polluting fuels (e.g. wood, kerosene) for household energy and typically work in the informal economy. In an informal settlement in Nairobi, surveys administered before (n=474) and after (n=194) a mandatory COVID-19-related community lockdown documented socioeconomic/household energy impacts. During lockdown, 95% of participants indicated income decline or cessation and 88% reported being food … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 40 publications
7
30
0
Order By: Relevance
“…On a monthly basis, the average amount spent by PAYG LPG residential customers (840 Ksh/month (US$7.69)) was similar to the paid amount reported by purchasers of LPG cylinder refills under the BCRM in the same community (850 Ksh/month (US$7.83)). 32 Similar average monthly expenditures among PAYG LPG customers despite lower usage of PAYG LPG (4 days/week) (Table 2) compared to self-reported use of LPG under the BCRM (6.3 days/week) 32 is due to a ∼7.1% fuel surcharge by PayGo Energy to cover equipment installation and delivery fees. 42,43…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…On a monthly basis, the average amount spent by PAYG LPG residential customers (840 Ksh/month (US$7.69)) was similar to the paid amount reported by purchasers of LPG cylinder refills under the BCRM in the same community (850 Ksh/month (US$7.83)). 32 Similar average monthly expenditures among PAYG LPG customers despite lower usage of PAYG LPG (4 days/week) (Table 2) compared to self-reported use of LPG under the BCRM (6.3 days/week) 32 is due to a ∼7.1% fuel surcharge by PayGo Energy to cover equipment installation and delivery fees. 42,43…”
Section: Discussionmentioning
confidence: 91%
“…Among 415 PAYG LPG residential customers, annual LPG per capita consumption was 11.6 kg/capita/year, below that of peri-urban dwellers (12.8 kg/capita/year) and of urban dwellers (18.7 kg/capita/year) reported in the 2019 Kenya LPG National Feasibility study of domestic fuel patterns. 41 32 is due to a ~7.1% fuel surcharge by PayGo Energy to cover equipment installation and delivery fees. 42,43 Additional to the flexible payment scheme offered by PAYG LPG, in interviews with customers it was revealed that increased safety from burns/gas explosions, time savings and ability to prepare separate dishes on both burners and fuel delivery were also key features enjoyed by households.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations